Gray matter changes in right superior temporal gyrus in criminal psychopaths. Evidence from voxel-based morphometry - Müller, Jürgen L.; Gänßbauer, Susanne; Sommer, Monika; Döhnel, Katrin; Weber, Tatjana; Schmidt-Wilcke, Tobias; Hajak, Göran (Psychiatry research. Neuroimaging, 2008)
“Psychopathy” according to the PCL-R describes a specific subgroup of antisocial personality disorder with a high risk for criminal relapses. Lesion and imaging studies point towards frontal or temporal brain regions connected with disturbed social behavior, antisocial personality disorder (APD) and psychopathy. Morphologically, some studies described a reduced prefrontal brain volume, whereas others reported on temporal lobe atrophy. To further investigate whether participants with psychopathy according to the Psychopathy Checklist — Revised Version (PCL-R) show abnormalities in brain structure, we used voxel-based morphometry (VBM) to investigate region-specific changes in gray matter in 17 forensic male inpatients with high PCL-R scores (PCL-R > 28) and 17 male control subjects with low PCL-R scores (PCL < 10). We found significant gray matter reductions in frontal and temporal brain regions in psychopaths compared with controls. In particular, we found a highly significant volume loss in the right superior temporal gyrus. This is the first study to show that psychopathy is associated with a decrease in gray matter in both frontal and temporal brain regions, in particular in the right superior temporal gyrus, supporting the hypothesis that a disturbed frontotemporal network is critically involved in the pathogenesis of psychopathy.